Tet3 is required for normal in vitro fertilization preimplantation embryos development of bovine. Issue 3 (20th January 2019) - Cheng, Hui; Zhang, Jian; Zhang, Sheng; Zhai, Yanhui; Jiang, Yu; An, Xinglan; Ma, Xiaoling; Zhang, Xueming; Li, Ziyi; Tang, Bo
Abstract : DNA methylation is a central epigenetic event that regulates cellular differentiation, reprogramming, and pathogenesis. DNA demethylation occurs in preimplantation embryos and primordial germ cells. Recent studies suggest that TET3‐mediated oxidation of 5‐methylcytosine (5‐mC) contributes to genome‐wide loss of DNA methylation, yet the mechanism of this process in bovine preimplanted embryos has remained unknown. In this study, we analyzed the expression of Tet gene family at different stages of embryo development. The results revealed that Tet3 was highly expressed in bovine oocytes and in vitro fertilization preimplantation embryos. Knockdown of Tet3 by injection of siRNA in germinal vesicle oocytes was used to assess its role in epigenetic remodeling and embryo development. The results showed that knockdown of Tet3 significantly inhibited oocyte development, maturation, fertilization, and decreased subsequently cleavage and blastocyst rates. Tet3 knockdown significantly increased 5‐mC levels, whereas the 5‐hmC levels slightly declined. The quantitative polymerase chain reaction data showed that expression levels of the pluripotency genes ( POU5F1 and NANOG ) were significantly decreased, but the imprinted gene H19 did not change in the Tet3 knockdown group. In addition, some pluripotency genes ( POU5F1 and NANOG ) and repeated elements ( satellite I and α‐satellite ) promoter regions showed hypermethylation in the Tet3 knockdown group, except the imprinted gene H19 . Furthermore, the percentage of apoptotic cells and the expression levels of the proapoptotic gene BAX were significantly increased, whereas the antiapoptotic gene BCL‐2 messenger RNA levels were decreased in the Tet3 knockdown group. Our results indicated that Tet3 could influence the expression level of the pluripotency genes through regulating the methylation status of the promoter region, thus affect embryonic development. Abstract : Tet3 can influence the expression level of the pluripotency genes through regulating the promoter region methylation status, and thus affect embryonic development.